Evaluation and monitoring the health of media staff using the occupational health management model - Mohseni, Hamidreza; Alimohammadzadeh , Khalil; Hosseini , Seyed Mojtaba; Maher , Ali (Researcher Bulletin of Medical Sciences, 2020)
Objective: Considering the necessity of creating, maintaining and promoting the health of employees as the main organizational capital, this study was conducted with the aim of comprehensive and complete observation of the health status of employees in individual, occupational and organizational dimensions in order to achieve a comprehensive occupational health management model. Materials and Methods: This study is an applied, qualitative and survey research in terms of objective, and is a qualitative study of survey and observational studies in terms of method, conducted during the years 2016 to 2018 in 300 workstations in 5 government buildings with sampling and snowball methods and data were collected with field method using technical apparatus and designed forms finalized by focus group discussions. Results: Creating a health management model resulted in creating a database on the individual health status of employees and their workplace health and creating a management dashboard for instant monitoring of organizational health status. Using this model, it was possible to evaluate and monitor the personal and occupational health of employees at any time. Conclusion: A managerial approach was achieved while classifying media related jobs by designing this occupational health model that, at each moment a clear, realistic and complete picture of the health status of the community was created and, strategies regarding the health status of the staff in accordance with the health status of the staff were adjusted, implemented and communicated